Efficient Resource Allocation and Computation Framework for Vehicular Multimedia Cloud Computing (International Journal of Food and Nutritional Sciences, 2022)
Wireless sensor networks playing a vital role in collaboration with it contemporary technologiessuch as cloud computing, IoT etc. This builds a smart technology everywhere. Sensor technologiesbecame heart to the transportation system that leads to the intelligent transportation system. Smartvehicles are integrated with a variety of sensing structures related to multimedia applications andtheir services related to weather, smart driving support, traffic details, road safety alerts and otherelectronic entertainment devices.